Socio-Demographic Predictors of Patient Satisfaction with OPD Services at a Private Hospital in Rural Nepal - Sah, Laxmi Narayan; Jain, Susmit (Journal of Multidisciplinary Research Advancements, 2025)
Patient satisfaction is a vital indicator of healthcare quality and is significantly influenced by socio-demographic factors. Understanding how these factors impact satisfaction helps healthcare providers improve service delivery. To investigate the relationship between socio-demographic variables and patient satisfaction with outpatient department (OPD) services at Shivdarshan Central Hospital Pvt. Ltd., Rautahat, Nepal, a descriptive cross-sectional study was done amongst 206 patients who attended the OPD. A structured questionnaire containing the PSQ-18 was utilised to collect data, including socio-demographic details and satisfaction ratings across diverse service areas. Data were cleaned in SPSS, and chi-square tests, ANOVA, and binary logistic regression were used to assess associations among variables. Overall, 81.6% of respondents reported satisfaction with OPD services. The highest satisfaction was observed in Technical Quality (mean=4.52±0.72) and Accessibility (mean=4.39±0.40) domains. Key modifiable factors significantly associated with satisfaction included waiting time ≤60 minutes (OR = 47.01, p < 0.001) and health insurance coverage (92.2% vs 71.2% satisfaction, p < 0.001). Socio-demographic factors strongly influencing satisfaction included wealth >40k NPR/month (OR=7.16, p=0.025), secondary education (88.2% vs 63.9% for illiterate, p=0.022), and male gender (88.8% vs 73.7%, p=0.005). Socio-demographic factors are among the most important predictors of patient satisfaction with OPD services. System-level inefficiencies, namely wait times and cost barriers, can be addressed through the implementation of customised interventions for segments by demographic groupings, thereby enhancing satisfaction and ensuring equitable, patient-focused care.